Optimal dynamic design of a planar slider-crank mechanism with a joint clearance. (April 2015) - Varedi, S.M.; Daniali, H.M.; Dardel, M.; Fathi, A.
Abstract: In general, in dynamic analysis of mechanisms, joints are assumed to be ideal without clearance. However, in reality, clearances in the joints are inevitable due to tolerances, and defects arising from design and manufacturing. When a joint clearance is introduced, the mechanism gains two uncontrollable degrees of freedom. Therefore, poor dynamic performance, reduction in components life and generation of undesirable vibrations result in the impacts of mating parts in the clearance joint. In this paper, an optimization method is proposed to alleviate the undesirable effects of joint clearance. The main consideration here is to optimize the mass distribution of the links of a mechanism to reduce or eliminate the impact forces in the clearance joint. An algorithm based on PSO solves this highly nonlinear optimization problem for a slider–crank mechanism with a revolute clearance joint between the slider and the connecting rod. Finally, an example is included to demonstrate the efficiency of the algorithm. Highlights: Joint clearance is the source of position error, shocks and vibrations. We alleviate the undesirable effects of joint clearance by mass re-distribution. An algorithm based on PSO solves the problem for a slider–crank mechanism. The accelerations and the contact forces for the optimal design are bounded.